Incorporating G-C pair-recognizing Guanidinium into PNAs for sequence and structure specific recognition of dsRNAs over dsDNAs and ssRNAs - Krishna, Manchugondanahalli S. (2021)
Recognition of RNAs under physiological conditions is important for the development of chemical probes and therapeutic ligands. Nucleobase-modified dsRNA-binding PNAs (dbPNAs) are promising for the recognition of dsRNAs in a sequence and structure specific manner under near-physiological conditions. Guanidinium is often present in proteins and small molecules for the recognition of G bases in nucleic acids, in cell-penetrating carriers, and in bioactive drug molecules, which might be due to the fact that guanidinium is amphiphilic and has unique hydrogen bonding and stacking properties. We hypothesized that a simple guanidinium moiety can be directly incorporated into PNAs to facilitate enhanced molecular recognition of G-C pairs in dsRNAs and improved bioactivity. We grafted a guanidinium moiety directly into a PNA monomer (designated as R) using a two-carbon linker as guided by computational modeling studies. The synthetic scheme of the PNA R monomer is relatively simple compared to that of the previously reported L monomer. We incorporated the R residue into various dbPNAs for binding studies. dbPNAs incorporated with R residues are excellent in sequence specifically recognizing G-C pairs in dsRNAs over dsDNA and ssRNAs. We demonstrated that the R residue is compatible with unmodified T and C and previously developed modified L and Q residues in dbPNAs for targeting model dsRNAs, the influenza A viral panhandle duplex structure, and the HIV-1 frameshift site RNA hairpin. Furthermore, R residues enhance the cellular uptake of PNAs.